Urgensitas Sumber Daya Pendukung Keberhasilan Dalam Pelaksanaan Kurikulum PAI - Suadi (Tarbawi : Jurnal Studi Pendidikan Islami, 2022)
This research aims to find out things that are very related and important in supporting success in implementing the curriculum. This research uses a library research method, namely research based on the opinions of educational experts. Important components as supporting resources for the successful implementation of the curriculum include the implementation of education management in the micro scope called school management, utilization of learning resources, teacher performance and professionalism. However, in the author's opinion, one of the most urgent things is micromanagement support. And the essence of school management lies in leadership. Because it is through intelligent leadership that curriculum planning, implementation and evaluation can be carried out effectively, efficiently, accountably and transparently.